2011
DOI: 10.1111/j.1365-3059.2011.02487.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenology on susceptibility of Norway spruce (Picea abies) to fungal pathogens

Abstract: Ceratocystis polonica and Heterobasidion parviporum are important fungal pathogens in Norway spruce (Picea abies). Tree susceptibility to these pathogens with respect to phenology was studied using artificial fungal inoculations at six stages of bud development, and assessed by measuring phloem necroses in the stems of 2-and 8-year-old trees. Tree capacity for resistance was assessed by measuring phloem nonstructural carbohydrates at each stage. Phloem necroses were significantly larger in trees with fungal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The heritability is somewhat lower than the estimates found for flushing scores in other progeny tests (e. g. Hannerz et al 1999;Skrøppa and Steffenrem 2015). The observed genetic correlation between the timing of flushing and C. polonica lesion lengths corresponds to what was found by Krokene et al (2012) who concluded that the level of susceptibility to this pathogen is related to tree phenology.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…The heritability is somewhat lower than the estimates found for flushing scores in other progeny tests (e. g. Hannerz et al 1999;Skrøppa and Steffenrem 2015). The observed genetic correlation between the timing of flushing and C. polonica lesion lengths corresponds to what was found by Krokene et al (2012) who concluded that the level of susceptibility to this pathogen is related to tree phenology.…”
Section: Discussionmentioning
confidence: 41%
“…C. Moreau) has not been conducted, both due to limited information about genetic variation in resistance to the fungi and due to lack of reliable selection techniques. During the last 20 years several studies have demonstrated the presence of a genetic component in susceptibility to Heterobasidion, based on variation in lesion lengths after stem inoculation with the fungus Stenlid 1996, 1997;Swedjemark and Karlsson 2004;Swedjemark et al , 2001Arnerup et al 2010;Krokene et al 2012;Skrøppa et al 2014). Most of these studies were based on differently aged clonal material.…”
Section: Introductionmentioning
confidence: 99%
“…data). The seasonal growth rhythm stage at the time of inoculation, indicated by the phenology of apical meristems, is known to influence the results and could cause differences in observed variances and GxE interactions (Krokene et al 2012;Skrøppa et al 2015b;Swedjemark and Stenlid 1996). This vulnerability to environmental factors acting on the inoculum batch itself, or the trees tested, makes it important to design studies that include more than one test site, both parents and offspring, or different inoculum, to obtain an estimate of the repeatability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of E. polonica is a frequently applied method for testing the capacity of trees to avert biotic invaders and to mobilise defences (Lieutier et al 2003;Krokene et al 2012). The long co-evolution of this pathogen with Norway spruce is substantiated by local and systemic induction of resistance marker genes in response to infection (Fossdal et al 2012).…”
Section: Discussionmentioning
confidence: 99%